Evaluation of digital and manual orthodontic diagnostic setups in non-extraction cases using ABO model grading system: an in-vitro study - Sherwet Shakr; Ibrahim Negm; Hatem Saifeldin (BMC Oral Health, 2024)
Abstract Background To evaluate the outcome quality of manual and digital orthodontic diagnostic setups in non-extraction cases according to the American Board of Orthodontics model grading system and to calculate the laboratory time needed for orthodontic diagnostic setup construction. Methods The sample consisted of 60 pretreatment models of non-extraction orthodontic cases with age ranges of 18–30. The study models were duplicated and scanned with 3Shape R-750 scanner. Digital and manual diagnostic setups were constructed according to their respective treatment plans. Digital diagnostic setups were 3D printed and then both manual and digital setups were assessed using the modified American Board of Orthodontics Cast Radiograph evaluation score (ABO CRE), which includes alignment, marginal ridge, buccolingual inclination, occlusal contacts, occlusal relationships, interproximal contacts, and overjet. The laboratory time needed for orthodontic setups was measured in minutes. Results The total ABO CRE score of the digital diagnostic setup group (5.93 ± 2.74) was significantly lower than that of the manual diagnostic setup group (13.08 ± 3.25). The manual diagnostic setup had significantly larger scores in marginal ridge, overjet, overbite, buccolingual inclination, occlusal relationship, and total scores (P < 0.01). However, the digital diagnostic setup had a statistically larger occlusal contacts score than the manual diagnostic setup (P < 0.01). There was no significant difference between the alignment and the interproximal contacts scores in either group. The manual diagnostic setup needed significantly longer laboratory time (187.8 ± 14.22) than the digital setup (93.08 ± 12.65) (P < 0.01). Comparison between broken teeth was performed by using the chi-square test which found no significant difference between different tooth types. Conclusions Digital diagnostic setup is a reliable tool for orthodontic diagnostic setup construction providing excellent quality setup models. Manual diagnostic setup is time consuming with a technique-sensitive laboratory procedure.